' … One of the Most Severe Duties … ': Landscapes of Timber-getting at a Former Tasmanian Convict Station. (2nd July 2020) - Tuffin, Richard; Gibbs, Martin; Clark, Don; Clark, Marcus; Rigozzi, Peter
ABSTRACT: The British colonisation of Australia was made possible by its co-option of unfree labour. Unwillingly placed at the leading edge of the colonising wave, the convict provided the labour power and skill through which land was alienated from its original inhabitants, infrastructure created and services rendered. A key feature of this process was the clearance, 'improvement' and targeted harvesting of the thickly timbered parts of the colonies. Combining heavy manual labour and skilled craft, timber-getting quickly became a staple task of convicts both in private and public service. This paper examines the deployment of convict labour by the government, focussing predominantly on the former convict probation station of Cascades, on the Tasman Peninsula, Tasmania (1842–55). The way in which the administrators achieved punitive and economic aims is examined using the archaeological, historical and architectural record. Documentary and archaeological evidence is used to understand the timber-getting processes, and how penological requirements were incorporated. The paper also examines the timber resources that the convicts were required to extract and convert, shedding more light on the motives and processes of attainment.